Prevalence and Factors Influencing Alcohol Use in Pregnancy among Women Attending Antenatal Care in Dodoma Region, Tanzania: A Cross-Sectional Study. (18th October 2018) - Mpelo, Matunga; Kibusi, Stephen Matthew; Moshi, Fabiola; Nyundo, Azan; Ntwenya, Julius Edward; Mpondo, Bonaventura C. T.
Abstract : Background . Alcohol use during pregnancy is high despite the well-established evidence on its adverse pregnancy outcomes and poor child development. Early identification and behavioural modification are of great significance. This study aimed to determine the prevalence and associated factors of alcohol use during pregnancy among women in Dodoma region. Methods . 365 randomly selected pregnant women attending antenatal care services in Dodoma region were included. Structured questionnaires were used to assess sociodemographic characteristic and alcohol use. Both descriptive and inferential analyses were used to estimate the prevalence and independent relationships of factors associated with alcohol use in pregnancy, respectively. Results . Results showed a prevalence of 15.1% out of the 365 women attending antenatal services in Dodoma region. Prepregnancy alcohol use and having relatives who use alcohol were associated with alcohol use (AOR= 5.19; 95% CI: 4.791-34.867 and AOR=1.57; 95% CI: 1.393-6.248), respectively. Moreover, other associated factors included low education status (AOR=10.636; 95% CI: 1.89-19.844), making local brews as a source of income (AOR=11.44; 95% CI: 1.008-19.86), and not having had complications in previous pregnancies (AOR=4.93; 95% CI: 1.031-23.59). Conclusion . There is a significantly high prevalence of alcohol use during pregnancy in Dodoma. Social networks and low social, economic status were associated with alcohol use in pregnancy. There is a need for public health interventions to address alcohol use particularly targeting women of reproductive age with low socioeconomic status.